Boussargues (Argelliers, Hérault) Un habitat ceinturé chalcolithique : les fouilles du secteur ouest - Colomer, Albert (Documents d'archéologie française, 1990)
This book is the first volume of the exhaustive publication of the excavations carried out in Boussargues, located near Montpellier and a majorsite of the Fontbouisse Chalcolithic culture (2500 BC). It includes the study of the natural and cultural surrounding of the site, and the study of the achieved excavation of the West area and its three habitations. The architecture of the buildings, the organization of the domestic space and the settlement in its natural and economical context are the three major orientations. Thanks to a versatile research team, the conclusions drawn are a fundamental contribution to the understanding of the Neolithic cultures from Southern France.